Introduction to Immersive Video Technologies - Alain, Martin; Zerman, Emin (Elsevier, 2022)
Immersive imaging technologies have become a topic of great interest in recent years due to the convergence of maturing research from different fields and broad aspects of signal and image processing, including but not limited to: computer vision, computer graphics, computational imaging, optics, and recent advances in deep learning. In particular, recent research and developments in these areas helped achieve better or faster content creation and image/video processing. This enables the design of complete practical systems covering capture to display for immersive imaging. In this chapter, we provide the theoretical background for the rest of the book and introduce key concepts commonly used for traditional imaging systems and immersive video technologies. We also describe the stages of the immersive imaging technologies from content capture to display and quality assessment for three immersive imaging technologies: omnidirectional video, light fields, and volumetric (also known as free-viewpoint) video.1
Keywords: Immersive imaging; Plenoptic function; Omnidirectional video; Light field; Volumetric video; Point cloud; Textured mesh; Content delivery pipeline